Measuring Company Performance using the Balanced Scorecard (BSC) Method in Hydroponic Vegetable Agribusiness in Surabaya - Kusriningtyas, Destin Fitriah; Maulidah, Silvana; Ilmi Pariasa, Imaniar; Dina Riana, Fitria (Profit: Jurnal Adminsitrasi Bisnis, 2025)
Hydroponic farming has become increasingly popular since 2014 due to the increased accessibility of information and the efficient use of resources. Kebun Sayur Surabaya (KSS) is a producer and supplier of hydroponic vegetables experiencing changes in its business dynamics. Problems such as the continuing impact of the pandemic affecting the company's operations and the increasing competence of similar businesses require companies to improve performance to remain competitive. Performance measurement can be done using the Balanced Scorecard (BSC) method, which considers all four perspectives: financial, customer, internal business processes, and learning and growth. The purpose of this study is to evaluate the performance of KSS using the BSC method by considering four perspectives. Data was obtained through interviews, questionnaires, company financial data and related journal references. The analysis results show that KSS has been optimal in all four perspectives; overall financial performance and customer satisfaction have increased significantly, although some aspects have decreased in other perspectives. Some strategies to improve and increase business performance for industry players are obtained based on the results of the analysis that has been carried out.